The Effect of Extraction Method on Total Flavonoid Content of Hedyotis corymbosa L. - Ulvia, Rengganis; Nurhasanah, Devika; Camelia, Azhar; Widianingrum, Lucia (Universitas Ahmad Dahlan, 2025)
Hedyotis corymbosa L. (H. corymbosa) is an Indonesian herbal plant with many health benefits. This activity comes from secondary metabolite compounds, one of which is flavonoids. These compounds can be obtained through an extraction process, where the extraction method is one of the factors that can affect the levels of compounds. This study aims to determine the effect of conventional extraction methods: maceration and soxhletation with non-conventional methods, Ultrasound Assisted Extraction (UAE) on the total flavonoid content of H. corymbose. The sample was extracted using 70% ethanol solvent (1:10 w/v) with the maceration, soxhletation, and UAE methods. The total flavonoid content of the H. corymbosa extract was measured using UV-Vis spectrophotometry. The data obtained were then analyzed statistically using SPSS One-Way ANOVA, followed by Post Hoc Tukey with a 95% confidence level. The soxhletation method has the highest flavonoid content at 72.255±1.334 mg QE/g, followed by UAE at 69.118±1.782 mg QE/g, and maceration at 43.725±0.679 mg QE/g. Statistical analysis confirmed that the extraction method significantly influences total flavonoid content. While both soxhletation and UAE methods produced similarly high flavonoid contents, UAE offers a substantial advantage in efficiency due to its shorter extraction time, making it a promising alternative to conventional soxhletation.